USING IN-VITRO MATURATION OF IMMATURE OOCYTES RETRIEVED FROM POOR RESPONDER PATIENTS TO IMPROVE PREGNANCY OUTCOMES IN SULAIMANI GOVERNMENT REGION, IRAQ - Kani Muhammed Falah; Hiwa Banna; Ismaeel H.A. Aghaways; Amanj Rahem Zangana; Farman Latif Mohammad (European Scientific Journal, ESJ, 2014)
Background and Aim: This study is conducted to evaluate whether in-vitro maturation of immature oocytes retrieved from stimulated cycles can help to increase the number of embryos available for transfer and whether transfer of embryos derived from in-vitro matured oocytes would contribute to better clinical outcomes of poor responder patients in ovarian stimulated cycles. PatientsandMethods: The present study was approved by the ethics committee in the College of Medicine,University of Sulaimani, Sulaimani, Kurdistan Government region, Iraq. Written informed consent was obtained, in which patients informed and understood to share the outcomes of their cycles for research purposes. The present study includes 92 poor responder cycles for intra cytoplasmic sperm injection. It comprises three and less mature oocytes (Metaphase II stage) with at least one immature oocyte (Metaphase I and Prophase I stage) which are retrieved after follicle aspiration and cycles are split into two groups control group (n=51), in which only mature oocytes are used, and in-vitro maturation (IVM) group (n=41) where the immature oocytes are matured in-vitro and used, then the outcomes are compared. In in-vitro maturation group, oocytes are classified based on nuclear maturation status in to mature (Metaphase II) and immature oocytes (Metaphase I and Prophase I). The rates of in-vitro maturation, fertilization, and high-quality embryos are compared. Results: Between the control group and in-vitro maturation group, no differences are observed as far as the implantation rate is concerned (12.5%, 12.5% respectively, p >0.05), while the in-vitro maturation group has a higher number of transferred embryos than the control group (1.54±1.12, 1.1±0.9, respectively, p<0.05), a higher pregnancy rate (21.9%, 18.9%, respectively, p<0.05), with a lower embryo transfer cancellation rate (21.9%, 27.45% respectively, p<0.05). In in-vitro maturation group, immature oocytes have lower fertilization rate (40.47% versus 58.33%) with (p <0.05), higher high-quality embryos (64.7% versus 51.43%) with (p< 0.05) and no difference between Metaphase I and Prophase I in the rates of in-vitro maturation, fertilization and high-quality embryos. Conclusion: The results show that human immature oocytes recovered from stimulated cycles can be matured, fertilized and developed in-vitro but they have lower fertilization rate than the in-vivo matured oocytes. Embryos derived from in-vitro matured oocytes may contribute to the better outcome in poor responder cycles.